2020
DOI: 10.1007/s10900-020-00804-0
|View full text |Cite
|
Sign up to set email alerts
|

Building a Culture of Health at the Neighborhood Level Through Governance Councils

Abstract: To explore facilitators and barriers to developing and sustaining collaboration among New York City Department of Health and Mental Hygiene's Neighborhood Health Action Centers and co-located partners, who share information and decisionmaking through a Governance Council structure of representative members. Semi-structured interviews were conducted in 2018 with 43 Governance Council members across the three Action Centers of East Harlem (13), Tremont (15), and Brownsville (15), New York City. Governance Counci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…Conducted as part of a mixed-methods evaluation, 28 the effort to survey visitors to the East Harlem Action Center contributed to a more robust understanding of this initiative by providing insight into client characteristics and experiences with Action Center services and programs. Most visitors surveyed reported positive experiences, with key indicators of satisfaction with the provider from their visit nearly universally met, including perceptions of receiving high quality care, being treated with respect, being made to be feel comfortable, and receiving effective communication.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Conducted as part of a mixed-methods evaluation, 28 the effort to survey visitors to the East Harlem Action Center contributed to a more robust understanding of this initiative by providing insight into client characteristics and experiences with Action Center services and programs. Most visitors surveyed reported positive experiences, with key indicators of satisfaction with the provider from their visit nearly universally met, including perceptions of receiving high quality care, being treated with respect, being made to be feel comfortable, and receiving effective communication.…”
Section: Discussionmentioning
confidence: 99%
“…In qualitative interviews conducted across the Action Centers, partners reported that being part of the Action Center meant that their clients received increased access to community resources and referrals, and that many clients responded to positively to the Action Center’s aim to serve as an open space and came in repeatedly to access resources. 28 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was a place-based model designed to cater to the historic inequities in the city. Such models, through information and resource sharing, are found to encourage continuous and organic collaboration within and beyond the councils and include external community organizations such as New York City agencies which aid in health services delivery (Dannefer et al, 2019; Pierre et al, 2020).…”
Section: Ideas For Reimagining Citiesmentioning
confidence: 99%